2011
DOI: 10.1063/1.3585985
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic apparatus for study of near-field heat transfer

Abstract: For bodies spaced in vacuum at distances shorter than the wavelength of the thermal radiation, radiative heat transfer substantially increases due to the contribution of evanescent electromagnetic waves. Experimental data on heat transfer in near-field regime are scarce. We have designed a cryogenic apparatus for the study of heat transfer over microscopic distances between metallic and non-metallic surfaces. Using a mechanical positioning system, a planeparallel gap between the samples, concentric disks, each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 12 publications
1
37
0
Order By: Relevance
“…More recently, Kralik et al 307 carried out near-field measurements between tungsten surfaces, each 35 mm 110 in diameter, with a separation distance between ~ 1 m to 1 mm. The hot-side surface was maintained between 10-100 K and cold side maintained at 5 K. They reported a three orders of magnitude increase in the emittance between the two surfaces.…”
Section: Near-field Radiationmentioning
confidence: 99%
“…More recently, Kralik et al 307 carried out near-field measurements between tungsten surfaces, each 35 mm 110 in diameter, with a separation distance between ~ 1 m to 1 mm. The hot-side surface was maintained between 10-100 K and cold side maintained at 5 K. They reported a three orders of magnitude increase in the emittance between the two surfaces.…”
Section: Near-field Radiationmentioning
confidence: 99%
“…in near-field regime) the situation radically changes. Indeed, at this scale, evanescent photons which remain confined near the surface of materials are the main contributors to transfer and they participate via tunneling through the vacuum gap [1][2][3][4][5][6][7][8]. A significant heat-flux increase results from this transport.…”
Section: Introductionmentioning
confidence: 99%
“…Basu et al * simchi@alumni.iust.ac.ir have considered two semi-infinite plates separated by a vacuum gap of finite width, especially for 0.1 < d < 100 nm, and studied the dependency of maximum heat flux to the dielectric function and vacuum gap width [14]. In addition at subwavelength gap (i.e., in near field regime), it has been shown that, a significant increment of heat flux results from the evanescent photons which remain confined near the surface of the materials [15][16][17][18][19][20][21][22]. Messina et al, have considered a metal-like (ML) medium layer (with width, δ) between two silicon carbide (SiC) layers (with width, d) and studied the amplification of photon heat tunneling in this structure [23].…”
Section: Introductionmentioning
confidence: 99%